Platelet-Endothelial Cell Adhesion Molecule-1 (CD31), a Scaffolding Molecule for Selected Catenin Family Members Whose Binding Is Mediated by Different Tyrosine and Serine/Threonine Phosphorylation - Neta Ilan; Larry Cheung; Emese Pinter; Joseph A. Madri (2000)
Platelet-endothelial cell adhesion molecule (PECAM)-1 is a 130-kDa glycoprotein commonly used as an endothelium-specific marker. Evidence to date suggests that PECAM-1 is more than just an endothelial cell marker but is intimately involved in signal transduction pathways. This is mediated in part by phosphorylation of specific tyrosine residues within the ITAM domain of PECAM-1 and by recruitment of adapter and signaling molecules. Recently we demonstrated that PECAM-1/β-catenin association functions to regulate β-catenin localization and, moreover, to modulate β-catenin tyrosine phosphorylation levels. Here we show that: 1) not only β-catenin, but also γ-catenin is associated with PECAM-1in vitro and in vivo; 2) PKC enzyme directly phosphorylates purified PECAM-1; 3) PKC-derived PECAM-1 serine/threonine phosphorylation inversely correlates with γ-catenin association; 4) PECAM-1 recruits γ-catenin to cell-cell junctions in transfected SW480 cells; and 5) γ-catenin may recruit PECAM-1 into an insoluble cytoskeletal fraction. These data further support the concept that PECAM-1 functions as a binder and modulator of catenins and provides a molecular mechanism for previously reported PECAM-1/cytoskeleton interactions. Platelet-endothelial cell adhesion molecule (PECAM)-1 is a 130-kDa glycoprotein commonly used as an endothelium-specific marker. Evidence to date suggests that PECAM-1 is more than just an endothelial cell marker but is intimately involved in signal transduction pathways. This is mediated in part by phosphorylation of specific tyrosine residues within the ITAM domain of PECAM-1 and by recruitment of adapter and signaling molecules. Recently we demonstrated that PECAM-1/β-catenin association functions to regulate β-catenin localization and, moreover, to modulate β-catenin tyrosine phosphorylation levels. Here we show that: 1) not only β-catenin, but also γ-catenin is associated with PECAM-1in vitro and in vivo; 2) PKC enzyme directly phosphorylates purified PECAM-1; 3) PKC-derived PECAM-1 serine/threonine phosphorylation inversely correlates with γ-catenin association; 4) PECAM-1 recruits γ-catenin to cell-cell junctions in transfected SW480 cells; and 5) γ-catenin may recruit PECAM-1 into an insoluble cytoskeletal fraction. These data further support the concept that PECAM-1 functions as a binder and modulator of catenins and provides a molecular mechanism for previously reported PECAM-1/cytoskeleton interactions. platelet-endothelial cell adhesion molecule immunoreceptor tyrosine-based activation motif SH-2-containing protein-tyrosine phosphatase human umbilical vein endothelial cell(s) post coitus protein kinase C mitogen-activated protein kinase glutathione S-transferase immunoprecipitation 4-amino-5-(4 methylphenyl)-7-(t-butyl)pyrazolo[3,4-d]pyrimidine Platelet-endothelial cell adhesion molecule (PECAM-1, CD31)1 is a 130-kDa glycoprotein belonging to the Ig superfamily of cell adhesion molecules. PECAM-1 expression is restricted to cells of the vascular system platelets, monocytes, neutrophils, selected T cells, and endothelial cells (1.Newman P.J. J. Clin. Invest. 1997; 99: 3-8Crossref PubMed Scopus (432) Google Scholar). In the latter, PECAM-1 is localized to cell-cell borders of confluent monolayers and, in addition, to lumen-facing areas of blood vessels or tube-like endothelial structures formed in vitro (2.Ilan N. Mahooti P. Rimm D.L. Madri J.A. J. Cell Sci. 1999; 112: 3005-3014Crossref PubMed Google Scholar). PECAM-1 becomes diffusely distributed on the cell surface of sparse cell cultures or at the leading fronts of migrating cells (3.Schimmenti L.A. Yan H.-C. Madri J.A. Albelda S.M. J. Cell. Physiol. 1992; 153: 417-428Crossref PubMed Scopus (112) Google Scholar). PECAM-1 has been shown to be a key player in the adhesion cascade leading to extravasation of leukocytes during inflammation. Pretreatment of monocytes or neutrophils, as well as endothelial cells, with anti-PECAM-1 antibodies effectively inhibited transmigrationin vitro (4.Muller W.A. Weigel S.A. Deng X. Phillips D.M. J. Exp. Med. 1993; 178: 449-460Crossref PubMed Scopus (987) Google Scholar) and in vivo (5.Vaporciyan A.A. DeLisser H.M. Yan H. Mendiguren I.I. Thom S.R. Jones M.L. Ward P.A. Albelda S.M. Science. 1993; 262: 1580-1582Crossref PubMed Scopus (430) Google Scholar), indicating that PECAM-1 molecules on both the endothelial cells and the leukocytes contribute to the transmigration process. This was further supported by a genetic approach in PECAM-1 knockout mice, in which leukocytes are transiently arrested between the vascular endothelium and the basement membrane of inflammatory sites (6.Duncan G.S. Andrew D.P. Takimoto H. Kaufman S.A. Yoshida H. Spellberg J. de la Pompa J.L. Elia A. Wakeham A. Karan-Tamir B. Muller W.A. Senaldi G. Zukowski M.M. Mak T.W. J. Immunol. 1999; 162: 3022-3030PubMed Google Scholar). In addition, PECAM-1 knockout mice have been noted to suffer from prolonged bleeding times, which is at least in part due to disrupted endothelial-platelet interactions (53.Mahooti, S., Graesser, D., Patel, S., Newman, P. J., Duncan, G., Mak, T., and Madri, J. A. (2000) Am. J. Pathol., in pressGoogle Scholar), supporting the role of PECAM-1 as mediator of cell adhesion/activation. PECAM-1 has been shown to be more than just a passive player in adhesive interactions and indeed is actively involved in signal transduction pathways. PECAM-1 was demonstrated to undergo phosphorylation on tyrosine residues following mechanical (7.Osawa M. Masuda M. Harada N. Lopes R.B. Fujiwara K. Eur. J. Cell Biol. 1997; 72: 229-237PubMed Google Scholar) or biochemical (8.Lu T.T. Yan L.G. Madri J.A. Proc. Natl. Acad. Sci. U. S. A. 1996; 93: 11808-11813Crossref PubMed Scopus (97) Google Scholar, 9.Jackson D.E. Ward C.M. Wang R. Newman P.J. J. Biol. Chem. 1997; 272: 6986-6993Abstract Full Text Full Text PDF PubMed Scopus (199) Google Scholar, 10.Sagawa K. Kimura T. Swieter M. Siraganian R.P. J. Biol. Chem. 1997; 272: 31086-31091Abstract Full Text Full Text PDF PubMed Scopus (94) Google Scholar) stimulation. Specifically, an immunoreceptor tyrosine-based activation motif (ITAM) domain was recently identified in the cytoplasmic tail of PECAM-1 (11.Lu T.T. Barreuther M. Davis S. Madri J.A. J. Biol. Chem. 1997; 272: 14442-14446Abstract Full Text Full Text PDF PubMed Scopus (91) Google Scholar). Phosphorylation of specific tyrosine residues within the ITAM domain were found to mediate selective recruitment of adapter and signaling molecules. These include SH-2-containing protein-tyrosine phosphatase (SHP)-1 (12.Hua C.T. Gamble J.R. Vadas M.A. Jackson D.E. J. Biol. Chem. 1998; 273: 28332-28340Abstract Full Text Full Text PDF PubMed Scopus (116) Google Scholar) and -2 (9.Jackson D.E. Ward C.M. Wang R. Newman P.J. J. Biol. Chem. 1997; 272: 6986-6993Abstract Full Text Full Text PDF PubMed Scopus (199) Google Scholar), SHIP, phospholipase C-γ (13.Pumphrey N.J. Taylor V. Freeman S. Douglas M.R. Bradfield P.F. Young S.P. Lord J.M. Wakelam M.J.O. Bird I.N. Salmon M. Buckley C.D. FEBS Lett. 1999; 450: 77-83Crossref PubMed Scopus (92) Google Scholar), and phosphoinositide 3-kinase (14.Pellegatta F. Chierchia S.L. Zocchi M.R. J. Biol. Chem. 1998; 273: 27768-27771Abstract Full Text Full Text PDF PubMed Scopus (76) Google Scholar). Another set of proteins found to associate with PECAM-1 is represented by β-catenin (15.Matsumura T. Wolff K. Petzelbauer P. J. Immunol. 1997; 158: 3408-3416PubMed Google Scholar). Recently, we reported that PECAM-1/β-catenin association is regulated by β-catenin tyrosine phosphorylation (2.Ilan N. Mahooti P. Rimm D.L. Madri J.A. J. Cell Sci. 1999; 112: 3005-3014Crossref PubMed Google Scholar). Moreover, PECAM-1 overexpression resulted in recruitment of β-catenin into cell-cell junctions and a decrease in β-catenin tyrosine phosphorylation levels, suggesting that PECAM-1 plays active roles as a β-catenin modulator (2.Ilan N. Mahooti P. Rimm D.L. Madri J.A. J. Cell Sci. 1999; 112: 3005-3014Crossref PubMed Google Scholar). Here we present evidence that not only β- but also γ-catenin associates with PECAM-1. Interestingly, however, serine/threonine, rather than tyrosine, phosphorylation was found to be the major regulatory mechanism responsible for PECAM-1/γ-catenin association. We demonstrate a shift in γ-catenin localization from nuclear to cell-cell junctions upon stable PECAM-1 expression in SW480 colon carcinoma cells and, moreover, suggest that γ-catenin mediates recruitment of PECAM-1 into an insoluble, cytoskeletal fraction. These results confirm and further expand the concept of PECAM-1 being a binder and modulator of catenins. Human umbilical vein endothelial cells (HUVEC) were obtained from Jordan Pober (Yale Medical School) and were cultured in gelatin-coated flasks as described (2.Ilan N. Mahooti P. Rimm D.L. Madri J.A. J. Cell Sci. 1999; 112: 3005-3014Crossref PubMed Google Scholar, 16.Ilan N. Mahooti S. Madri J.A. J. Cell Sci. 1998; 111: 3621-3631Crossref PubMed Google Scholar). Hemangioendothelioma (EOMA) cells were obtained from Robert Auerbach (University of Wisconsin, Madison, WI) and were grown in complete Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum and antibiotics (17.Obeso J. Weber J. Auerbach R. Lab. Invest. 1990; 63: 259-269PubMed Google Scholar). MCF7 human breast adenocarcinoma cells were obtained from the American Type Culture Collection (HTB-22). The cells were grown in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum and 10 μg/ml insulin (bovine; Sigma) and transiently transfected as described (2.Ilan N. Mahooti P. Rimm D.L. Madri J.A. J. Cell Sci. 1999; 112: 3005-3014Crossref PubMed Google Scholar). SW480 human colon carcinoma cells stably expressing PECAM-1 cDNA were generated as described (2.Ilan N. Mahooti P. Rimm D.L. Madri J.A. J. Cell Sci. 1999; 112: 3005-3014Crossref PubMed Google Scholar) and were grown in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum. Embedding and culturing of HUVEC in three-dimensional type-I collagen gels was performed as described (16.Ilan N. Mahooti S. Madri J.A. J. Cell Sci. 1998; 111: 3621-3631Crossref PubMed Google Scholar). For cell migration assays, HUVEC were grown to confluency in 100-mm dishes. A 15-well minigel comb was used as a rake in a circular pattern to scrape cells from the dish leaving concentric rings of cells separated by intermittent cell-free regions. Cells were then allowed to migrate for 2 days before analyzed. Harvesting and in vitroculturing of murine conceptuses was performed as described previously (22.Pinter E. Barreuther M. Lu T. Imhof B.A. Madri J.A. Am. J. Pathol. 1997; 150: 1523-1530PubMed Google Scholar, 23.Pinter E. Mahooti S. Wang Y. Imhof B.A. Madri J.A. Am. J. Pathol. 1999; 154: 1367-1379Abstract Full Text Full Text PDF PubMed Scopus (54) Google Scholar). Briefly, conceptuses were collected from timed pregnant mice (CD1, Charles River, Wilmington, MA) using a dissecting microscope. Yolk sacs and embryos were separated in day 9.5 p.c. specimens. Groups of 50–60 embryos of day 7.5 p.c. conceptuses and 15 for day 9.5 p.c. conceptuses were analyzed. For glucose treatment, embryos were collected at day 7.5 p.c. and cultured in rat serum and in the absence or presence of 25 mmd-glucose as described (23.Pinter E. Mahooti S. Wang Y. Imhof B.A. Madri J.A. Am. J. Pathol. 1999; 154: 1367-1379Abstract Full Text Full Text PDF PubMed Scopus (54) Google Scholar). After 48 h, the yolk sacs were separated, lysed, and used for biochemical studies. Cell cultures were pretreated with 1 mmorthovanadate for 15 min at 37 °C, washed twice with ice-cold phosphate-buffered saline containing 1 mm orthovanadate and scraped into lysis buffer (50 mm Tris, pH 7.4, 150 mm NaCl, 1% Triton X-100, 1% Nonidet P-40, 0.5% deoxycholate, 1 mm orthovanadate, 1 mmphenylmethylsulfonyl fluoride, and a mixture of proteinase inhibitors; Roche Molecular Biochemicals). Soluble and insoluble cell fractions were made according to Simcha et al. (49.Simcha I. Shtutman M. Salomon D. Zhurinsky J. Sadot E. Geiger B. Ben-Ze'ev A. J. Cell Biol. 1998; 141: 1433-1448Crossref PubMed Scopus (236) Google Scholar). Total cellular protein concentration was determined by the BCA assay (Pierce) according to the manufacturer's instructions. 20 μg of cellular protein were fractionated on SDS-polyacrylamide gels, and protein immunoblotting was performed as described (16.Ilan N. Mahooti S. Madri J.A. J. Cell Sci. 1998; 111: 3621-3631Crossref PubMed Google Scholar). For immunoprecipitation, 100 μg of cellular protein were brought to volume of 1.0 ml in buffer containing 50 mm Tris, pH 7.5, 0.4 m NaCl, 5 mm EDTA, and 0.5% Nonidet P-40, preabsorbed with normal rabbit serum followed by protein A/G-Sepharose (Santa Cruz) precipitation. The cleared supernatant was incubated with the appropriate antibody for 2 h on ice followed by protein A/G-Sepharose immunoprecipitation. Beads were washed three times with the same buffer supplemented with 5% sucrose and once with the same buffer without sucrose and reduced salt concentration (50 mm NaCl). Sample buffer was then added, and after boiling, samples were subjected to gel electrophoresis and immunodetection as described. Rabbit polyclonal antibodies to human (BooBoo), and mouse (Sleet) PECAM-1 have been described previously (8.Lu T.T. Yan L.G. Madri J.A. Proc. Natl. Acad. Sci. U. S. A. 1996; 93: 11808-11813Crossref PubMed Scopus (97) Google Scholar, 22.Pinter E. Barreuther M. Lu T. Imhof B.A. Madri J.A. Am. J. Pathol. 1997; 150: 1523-1530PubMed Google Scholar, 23.Pinter E. Mahooti S. Wang Y. Imhof B.A. Madri J.A. Am. J. Pathol. 1999; 154: 1367-1379Abstract Full Text Full Text PDF PubMed Scopus (54) Google Scholar). Polyclonal antibodies to desmoplakin 1 and 2 were purchased from Serotec (Oxford, UK). Anti-phosphotyrosine (PY99), anti-PECAM-1 (C-20), anti-phosphorylated MAPK (E-4), and anti-Erk 2 (C14) antibodies were purchased from Santa Cruz Biotechnology. Polyclonal antibodies to PKC and phospho PKC (pan) were purchased from Upstate Biotechnology, Inc. (Lake Placid, NY). Monoclonal antibodies to β−catenin and SHP-2 (also known as PTP1D) were purchased from Transduction Laboratories (Lexington, KY). Other monoclonal antibodies included anti-vimentin (clone Vim 3B4, Dako), anti-γ-catenin (clone 15F11, Sigma) used for immunoblotting and anti-γ-catenin (clone PG-11E4, Zymed Laboratories Inc.) used for immunostaining. PP1, bisindolylmaleimide GF 109203x, staurosporine, and 1,2-dioctanoyl-sn-glycerol, a diacylglycerol analog (Calbiochem, La Jolla, CA), were dissolved in Me2SO to a concentration of 5 mm and used at final concentrations of 1, 1, 0.1, and 5 μm, respectively. Matching volumes of Me2SO were added to cell cultures as controls. Wild type or Tyr to Phe mutations at Tyr663, Tyr686, and Tyr701 of the full-length (8.Lu T.T. Yan L.G. Madri J.A. Proc. Natl. Acad. Sci. U. S. A. 1996; 93: 11808-11813Crossref PubMed Scopus (97) Google Scholar) or truncated (lacking the ectodomain (41.Kim C.S. Wang T. Madri J.A. Lab. Invest. 1998; 78: 583-590PubMed Google Scholar)) human PECAM-1 cDNA in the expression vector pcDNA3 were used. For stable expression of PECAM-1, SW480 and 293 cells were transfected with the FuGENE 6 reagent (Roche Molecular Biochemicals), and cells were selected with G418 (400 μg/ml) for 4 weeks, expanded, and stained with anti-PECAM-1, β-catenin, and γ-catenin antibodies as described (2.Ilan N. Mahooti P. Rimm D.L. Madri J.A. J. Cell Sci. 1999; 112: 3005-3014Crossref PubMed Google Scholar). 10 μl of PECAM-1/GST fusion protein, comprised of the full cytoplasmic PECAM-1 domain fused to GST as described (11.Lu T.T. Barreuther M. Davis S. Madri J.A. J. Biol. Chem. 1997; 272: 14442-14446Abstract Full Text Full Text PDF PubMed Scopus (91) Google Scholar), were incubated with 1.5 units of Src kinase (Upstate Biotechnology, Inc.) in kinase buffer (20 mmHepes, pH 7.4, 10 mm MgCl2, 10 mmMnCl2, 10% glycerol, and 30 μm ATP) for 20 min at 30 °C. PECAM-1/GST fusion protein was similarly phosphorylated with purified 1 unit of nPKCε enzyme (Life Technologies, Inc.) with a PKC phosphorylation kit according to the manufacturer's (Upstate Biotechnology, Inc.) instructions. One-tenth of the reaction was used for immunoblotting with anti-phosphotyrosine antibodies or for autoradiography (when using [32P]ATP; Amersham Pharmacia Biotech), and the rest of the reaction products were used for pull-down experiments. PECAM-1/GST fusion protein coupled to glutathione-agarose beads (10 μl) was added to 1 ml of binding buffer (50 mm Tris, pH 7.5, 150 mm NaCl, 5 mm EDTA, 0.5% Nonidet P-40, and 0.1 mg/ml bovine serum albumin) and incubated on ice for 10 min before the addition of 100 μg of HUVEC lysate. Samples were incubated on ice for additional 30 min, with occasional mixing by inversion, followed by centrifugation. The supernatant was saved, and 20 μl were run in parallel with the bead pellets. The pellet beads were washed twice with binding buffer supplemented with 0.4 m NaCl (final concentration) and once with binding buffer before the addition of sample buffer, boiling, and SDS-polyacrylamide gel electrophoresis. HUVEC three-dimensional cultures were fixed with 4% paraformaldehyde in phosphate-buffered saline overnight, dehydrated in a series of 50–100% ethanol, cleared in xylene, and embedded in paraffin. 5-μm sections were cut, mounted onto slides, deparaffinized, rehydrated, and stained. Immunohistochemical analysis of the standard 5-μm sections was done as described (2.Ilan N. Mahooti P. Rimm D.L. Madri J.A. J. Cell Sci. 1999; 112: 3005-3014Crossref PubMed Google Scholar). Briefly, sections were subjected to antigen retrieval, blocked with 10% normal donkey serum and double-stained overnight using a goat anti-human PECAM-1 (C-20, Santa Cruz) antibodies and a monoclonal antibody to vimentin. Sections were then extensively washed with TBS-Triton X-100 (0.01%) and subjected to secondary, donkey anti-goat fluorescein isothiocyanate, and donkey anti-mouse CY3-conjugated antibodies (Jackson ImmunoResearch, West Grove, PA) for 1 h, washed, and coverslipped. Cultures of HUVEC or SW480 cells, grown on glass coverslips, were fixed with 4% paraformaldehyde for 20 min, permeabilized for 1 min with 0.5% Triton X-100, and immunofluorescence stained as described (2.Ilan N. Mahooti P. Rimm D.L. Madri J.A. J. Cell Sci. 1999; 112: 3005-3014Crossref PubMed Google Scholar). For migrating cell staining, cells were grown on the coverslip to confluency and scraped in the middle in a cross-like pattern. Cells were allowed to migrate for 2 days before staining. All experiments were repeated at least twice with similar results. The PECAM-1 cytoplasmic domain sequence was examined for consensus PKC substrate sites using the ScanProsite-Protein against PROSITE program (ISREC bioinformatics server, Lausanne, SW). We had recently reported that PECAM-1 functions as a reservoir for and a modulator of tyrosine phosphorylated β-catenin (2.Ilan N. Mahooti P. Rimm D.L. Madri J.A. J. Cell Sci. 1999; 112: 3005-3014Crossref PubMed Google Scholar). Given the structural and functional similarities between β-catenin and γ-catenin (plakoglobin), we asked whether γ-catenin would similarly associate with PECAM-1 and investigated potential mechanisms that might be involved in the regulation of such an interaction. Previously, we found that PECAM-1/β-catenin interactions correlate with β-catenin tyrosine phosphorylation. As illustrated in Fig.1, β-catenin association with PECAM-1 was higher in EOMA cells compared with HUVEC, whereas no association was detected in transfected MCF7 cells (Ref. 2.Ilan N. Mahooti P. Rimm D.L. Madri J.A. J. Cell Sci. 1999; 112: 3005-3014Crossref PubMed Google Scholar and Fig. 1 A). Interestingly, in the same cell culture model system, PECAM-1/γ-catenin association showed the exact opposite phenotype, being highest in HUVEC (Fig. 1 A). This would suggest that not only β-catenin but also γ-catenin is a PECAM-1 partner and that PECAM-1 interaction with the two catenins is differentially regulated. It has been reported that Arm catenins (p120, β-catenin, and γ-catenin) are a major substrate targets for receptor and Src family kinases (18.Daniel J.M. Reynolds A.B. Bio Essays. 1997; 19: 883-891Crossref PubMed Scopus (285) Google Scholar). Therefore, to further study the potential role of γ-catenin tyrosine phosphorylation in its ability to associate with PECAM-1, HUVEC were treated with PP1, a specific inhibitor of Src kinase family members (19.Hanke J.H. Gardner J.P. Dow R.L. Changelian P.S. Brissette W.H. Weringer E.J Pollok B.A. Connelly P.A. J. Biol. Chem. 1996; 271: 695-701Abstract Full Text Full Text PDF PubMed Scopus (1784) Google Scholar). Immunoprecipitation (IP) studies revealed that although γ-catenin tyrosine phosphorylation levels were significantly reduced in PP1- treated HUVEC (Fig. 1 B,top panel), its association with PECAM-1 remain unchanged (Fig. 1 B, third panel). In contrast, β-catenin association with PECAM-1 was completely abolished after PP1 treatment (Fig. 1 B, fourth panel), supporting the concept that β-catenin tyrosine phosphorylation is the major factor for its interaction with PECAM-1. Interestingly, low but detectable levels of desmoplakin were co-IP with PECAM-1 independently of γ-catenin phosphotyrosine state, (Fig. 1 B, fifth panel), suggesting that γ-catenin interactions with PECAM-1 may mediate complex interactions with other structural protein families (see below). To further analyze the potential role of PECAM-1 tyrosine phosphorylation for its interaction with γ-catenin, purified GST-PECAM-1 fusion protein was phosphorylated ex vivo with Src enzyme (Ref. 11.Lu T.T. Barreuther M. Davis S. Madri J.A. J. Biol. Chem. 1997; 272: 14442-14446Abstract Full Text Full Text PDF PubMed Scopus (91) Google Scholar and Fig. 1 C, third panel). Pull-down experiments of HUVEC lysates were than performed with phosphorylated or nonphosphorylated GST-PECAM-1 fusion protein. As shown in Fig. 1 C (top panel), PECAM-1 tyrosine phosphorylation had no effect on γ-catenin recruitment, suggesting that neither γ-catenin (Fig. 1 B) or PECAM-1 (Fig.1 C) tyrosine phosphorylation is necessary for their interaction. Interestingly, although γ-catenin was mainly present in the pellet fraction, β-catenin was unable to interact with PECAM-1 and was mainly detected in the supernatant fraction (Fig.1 C, second panel), suggesting that under these conditions γ-catenin but not β-catenin is the major PECAM-1 partner, and in agreement with our previous IP experiments (Fig.1 A). Although much of the recent interest in PECAM-1 function arose from its tyrosine-based ITAM domain (11.Lu T.T. Barreuther M. Davis S. Madri J.A. J. Biol. Chem. 1997; 272: 14442-14446Abstract Full Text Full Text PDF PubMed Scopus (91) Google Scholar), PECAM-1 was initially characterized to be phosphorylated mainly on serine residues (20.Newman P.J. Hillery C.A. Albrecht R. Parise L.V. Berndt M.C. Mazurov A.V. Dunlop L.C. Zhang J. Rittehouse S.E. J. Cell Biol. 1992; 119: 239-246Crossref PubMed Scopus (124) Google Scholar). However, the role of serine/threonine phosphorylation for PECAM-1 function at the cellular or molecular level has not yet been reported. Incubation of our GST-PECAM-1 fusion protein with purified PKC enzyme resulted in significant PECAM-1 phosphorylation (Fig. 2 A,bottom panel), whereas no 32P incorporation was observed with GST alone (data not shown). To our knowledge, this is the first evidence that PKC can directly phosphorylate PECAM-1. Pull-down experiments with the PKC-derived phosphorylated and nonphosphorylated GST-PECAM-1 fusion protein and endothelial cell lysates indicated a significant decrease (more than 6-fold based on densitometric analysis, Fig. 2 B) in the ability of γ-catenin to bind PECAM-1 (Fig.2 A, top panel). In agreement with our previous finding (Fig. 1 C), β-catenin was only detected in the supernatant fractions (Fig. 2 A, second panel), suggesting that PKC exclusively modulates γ-catenin but not β-catenin interactions with PECAM-1. To further evaluate the role of PKC on PECAM-1/β-/γ-catenin interactions in the context of a cell system, we took advantage of the cell culture model presented in Fig. 1 A. High levels of PECAM-1/γ-catenin association in HUVEC may be due to low PKC activity in these cells. Indeed, exposure of HUVEC to a physiologic PKC inducer, diacylglycerol analog, significantly decreased PECAM-1/γ-catenin interactions (Fig. 2 C), more than 3-fold based on densitometric analysis (Fig. 2 D). Staurosporine, a potent PKC inhibitor, did not affect PECAM-1/γ-catenin interactions (Fig.2 C), further supporting the concept that PKC activity in HUVEC is low. In contrast, exposure of EOMA cells to bisindolylmaleimide GF-109203x (bis), a potent and selective PKC inhibitor (21.Toullec D. Pianetti P. Cosre H. Bellevergue P. Grand-Perret T. Ajakane M. Baudet V. Boissin P. Boursier E. Loriolle F. Duhamel L. Charon D. Kirilovsky J. J. Biol. Chem. 1991; 266: 15771-15781Abstract Full Text PDF PubMed Google Scholar), resulted in a substantial increase in PECAM-1/γ-catenin association (Fig. 2 E, top panel). Interestingly, the increase in γ-catenin binding was accompanied by a comparable decrease in β-catenin association with PECAM-1 (Fig. 2 E, middle panel). This lends further support to our pull-down (Figs. 1 C and2 A) and IP (Fig. 1 A) experiments in which γ-catenin had a higher affinity for PECAM-1. In contrast, the PECAM-1/SHP-2 interaction remained unchanged (Fig. 2 E,third panel), suggesting that although β-catenin and γ-catenin may compete for a common binding site/domain, the SHP-2-binding site is different (tyrosine residues 663/686 in the ITAM domain) and is not influenced by the catenins binding on PECAM-1. Taken together, our in vitro model systems support the concept of an inverse correlation between PECAM-1 serine/threonine phosphorylation and its ability to associate with γ-catenin and, moreover, may indicate that PECAM-1 is an in vivo PKC substrate. Given the ex vivo and in vitro ability of PECAM-1 to bind γ-catenin, we sought an analogous interaction in vivo. Significant increases in extraembryonic and embryonic vasculogenesis, with a concomitant decrease in PECAM-1 tyrosine phosphorylation levels have been characterized between days 7.5 and 9.5 p.c. of the developing murine conceptus (22.Pinter E. Barreuther M. Lu T. Imhof B.A. Madri J.A. Am. J. Pathol. 1997; 150: 1523-1530PubMed Google Scholar). Lysates, made from the whole conceptus at days 7.5 and 8.5 p.c. or yolk sac lysates from day 9.5 p.c. embryos were IP for PECAM-1, followed by γ-catenin immunoblotting. γ-Catenin was noted to be associated with PECAM-1 at all stages (Fig.3 A, top panel). However, an increase in PECAM-1/γ-catenin association occurred between days 7.5 and 9.5 p.c., a stage during which there is an increase in yolk sac blood island formation and simultaneous formation of embryonic vasculature. Interestingly, immunoblot analysis of the same lysate samples revealed a marked decrease in phospho PKC reactivity (Fig. 3 A, third panel), whereas PKC expression levels were similar (Fig. 3 A, fourth panel). As a control, the same membrane was striped and reprobed with an antibody for the phosphorylated MAPK. No changes in phosphorylated MAPK levels were detected between days 7.5 and 8.5 p.c. (Fig. 3 A, fifth panel), suggesting that the observed decrease in P-PKC reactivity is specific. Densitometric analysis of PECAM-1/γ-catenin co-IP and P-PKC reactivity during these stages of murine conceptuses development are summarized in Fig.3 B. These observations further support the ex vivo/in vitro inverse correlation between PECAM-1 serine/threonine phosphorylation and its ability to bind γ-catenin. We have recently reported that hyperglycemia causes yolk sac and embryonic vasculopathy in cultured murine conceptuses (23.Pinter E. Mahooti S. Wang Y. Imhof B.A. Madri J.A. Am. J. Pathol. 1999; 154: 1367-1379Abstract Full Text Full Text PDF PubMed Scopus (54) Google Scholar). Moreover, PECAM-1 was found to be hyper-phosphorylated on tyrosine residues in hyperglycemic day 9.5 p.c. yolk sacs compared with control embryos (23.Pinter E. Mahooti S. Wang Y. Imhof B.A. Madri J.A. Am. J. Pathol. 1999; 154: 1367-1379Abstract Full Text Full Text PDF PubMed Scopus (54) Google Scholar). Other reports have documented a glucose-induced PKC activity, and PECAM-1 phosphorylation in cultured endothelial cells (24.Rattan V. Shen Y. Sultana C. Kumar D. Kalra V. Am. J. Physiol. 1996; 271: E711-E717PubMed Google Scholar). To evaluate the potential glucose effect on PECAM-1/γ-catenin interactions, control, or glucose-treated day 9.5 p.c. yolk sac samples were IP for PECAM-1 followed by γ-catenin immunoblotting (Fig.3 C). A two-fold decrease in PECAM-1/γ-catenin association was noted in the glucose-treated samples (Fig. 3 C, top panel). In contrast, a significant increase in PECAM-1/SHP-2 association was detected after glucose exposure (Fig. 3 C,middle panel), in agreement with the glucose-induced increase in PECAM-1 tyrosine phosphorylation levels previously reported (23.Pinter E. Mahooti S. Wang Y. Imhof B.A. Madri J.A. Am. J. Pathol. 1999; 154: 1367-1379Abstract Full Text Full Text PDF PubMed Scopus (54) Google Scholar). In addition, glucose treatment induced a 4 fold increase in PKC phosphorylation, as judged by anti-phospho PKC immunoblotting (Fig.3 C, bottom panel), while PKC expression profile was similar (not shown). Thus, our ex vivo, in vitro, and in vivo studies all confirm the ability of γ-catenin to be associated with PECAM-1 and point to PECAM-1 serine/threonine phosphorylation, mediated, at least in part, by PKC as a major regulatory mechanism. Having demonstrated the PECAM-1/γ-catenin interaction biochemically, we were interested in the possible funct